The Literary Animal and the Grotesque Survival in Ted Hughes’s “Thrushes” (Journal of the College of Languages (JCL), 2017)
In his opus, Ted Hughes has annexed new and fresh territories of signification to the very notion of the literary animal. Building on the earlier modernist example of the Lawrencian legacy that dwells upon the question of animalism, Hughes seems to have stepped further into the terrain of the sheer struggle when, in his hands, the grotesquerie of survival and violence energizes the topos of the literary animal in his postmodern bestiary. In Hughes’s elemental poetic process this grotesquerie and violence stages the literary animal as a vital poetic device or motif that is finally restored to the primitive power of poetry. In his “Thrushes”, he thus defamiliarizes these tiny creatures’ acts of being to bring upfront into focus this power that has long been deadened and overshadowed by discursiveness and the ersatz, civilized acts of living.